Respons Pertumbuhan Bibit Bud Chips Tebu (Saccharum officinarum L.) terhadap Dosis dan Frekuensi Pemberian Pupuk N, P dan K pada Wadah Pembibitan yang Berbeda - Riki Rikardo Situmpul; Ferry Ezra Sitepu; Meiriani Meiriani (Universitas Sumatera Utara, 2015)
Provision of sugarcane seed with hight quality bud chips technic be affected by availability of nutriens in the soils requiring fertilization to nutrient requitments sugar cane seed. The research was conducted at nursery PT. Perkebunan Nusantara II Tanjung Jati, Binjai (40-50 meters above sea) from Mei-August 2014 using factorials split plot design with three factors: container nursery (polybag and pottray), dose fertilizer of N (Urea), P (SP-36), K (KCl) (6 g/60 plant, 12 g/60 plant, 18 g/60 plant) and frecuent fertilizer (2 times, 3 times, 4 times). The results showed using polybag effected significantly increase stem hight 32%, number of leaf 18%, stem diameters 48% and number of tillers 51% than using pottray. Dose fertilizers 18 g/60 plant effected significantly to stem hight, number of leaf and stem diameters of. Frecuent fertilizers not effected significantly to all of observed parameters.Keywords : Sugarcane, Containers nursery, Dose and Frecuent fertilizer